European Economy / Reform Issues in the Former Soviet Union: No 49 - Directorate For Economic And Financial Affairs; European Commission (1993)
Commission of the European Communities. Macroeconomics, Structural Reform Issues, The Inter-Republic Dimension, Political Economy and Economic Culture in the Transformation Process.